A facile and green approach to prepare monodispersion nanonickel nanofluids. (17th February 2018) - Yang, Shiwen; Tan, Yeqiang; Yin, Xianze; Wang, Luoxin; Wang, Hua; Zhou, Yingshan
ABSTRACT: This paper first develops a novel approach to prepare solvent-free nanonickel (Ni) nanofluids via hydrogen bonding between poly(ethylene oxide)- block -poly(propylene oxide)- block -poly(ethylene oxide) and 3-(Trimethoxysilyl)-1-propanethiol-modified Ni powder with average diameter of 80 nm to solve the problem of nanoparticles agglomerating due to the anisotropic dipolar attraction. It is interestingly found that Ni nanofluid is solid at room temperature while it undergoes solid–liquid transition without solvent at 50.7°C. The content of Ni is up to 12.1 wt%. The average diameter of core-shell structure of Ni nanofluids is 182 nm without agglomerations. It is worth noting that incorporation of Ni powder can elevate remarkably initial decomposition temperature of block copolymer due to high dispersity of Ni powder after modification. In addition, the viscosity of Ni nanofluids is found to be less than 10 Pa · s at 100°C, which is between that of water and honey, 0.001 and 10 Pa · s, respectively, at 20°C. More importantly, the Ni nanofluids exhibit excellent dispersion in water and other organic solvents for 2 months due to amphiphilic properties of the modifier molecule. These unique properties of Ni nanofluids may offer new scientific and technical opportunities for application of Ni powder in the form of liquid-like status.